2017
DOI: 10.3174/ajnr.a5468
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Lobe Malformations in Achondroplasia: Expanding the Brain Imaging Phenotype Associated withFGFR3-Related Skeletal Dysplasias

Abstract: Thanatophoric dysplasia, achondroplasia, and hypochondroplasia belong to the () group of genetic skeletal disorders. Temporal lobe abnormalities have been documented in thanatophoric dysplasia and hypochondroplasia, and in 1 case of achondroplasia. We retrospectively identified 13 children with achondroplasia who underwent MR imaging of the brain between 2002 and 2015. All children demonstrated a deep transverse temporal sulcus on MR imaging. Further common neuroimaging findings were incomplete hippocampal rot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 22 publications
(25 reference statements)
0
10
0
Order By: Relevance
“…8 ). Moreover, there may be primary forms due to genetic conditions such as FGFR3 ( Manikkam et al , 2018 ) and FGFR2 mutations ( Stark et al , 2015 ) as well as tubulin mutations ( Oegema et al , 2015 ; Mutch et al , 2016 ; Romaniello et al , 2018 ) ( Fig. 8A–D ), or secondary forms due to distortion of the sulcation pattern from presence or absence of nearby intracranial structures [such as in the case of stenogyria due to the absence of the cerebral falx in the Chiari II malformation ( Miller et al , 2008 )], or in the case of ACTA2 mutations where the rigidity of the abnormal arteries probably leads to an abnormal conformation of the mesial hemispheric sulci ( D’Arco et al , 2018 ) ( Fig.…”
Section: Malformations Of Cortical Development: Definitionsmentioning
confidence: 99%
“…8 ). Moreover, there may be primary forms due to genetic conditions such as FGFR3 ( Manikkam et al , 2018 ) and FGFR2 mutations ( Stark et al , 2015 ) as well as tubulin mutations ( Oegema et al , 2015 ; Mutch et al , 2016 ; Romaniello et al , 2018 ) ( Fig. 8A–D ), or secondary forms due to distortion of the sulcation pattern from presence or absence of nearby intracranial structures [such as in the case of stenogyria due to the absence of the cerebral falx in the Chiari II malformation ( Miller et al , 2008 )], or in the case of ACTA2 mutations where the rigidity of the abnormal arteries probably leads to an abnormal conformation of the mesial hemispheric sulci ( D’Arco et al , 2018 ) ( Fig.…”
Section: Malformations Of Cortical Development: Definitionsmentioning
confidence: 99%
“…Given that achondroplasia and hypochondroplasia belong to the same family of bone dysplasias [52], it would not be surprising to identify similar dysgenesis in occasional individuals with achondroplasia. In fact, that was recently reported by Manikkam et al [215] In neither disorder has the frequency of temporal lobe structural abnormalities been determined. Nor has the frequency with which temporal lobe dysgenesis results in seizures, or whether temporal lobe abnormalities are a marker for more severe central nervous system consequences of FGFR3 been determined.…”
Section: Natural History and Managementmentioning
confidence: 97%
“…Although far more common in those with hypochondroplasia [77], seizures occasionally arise in those with achondroplasia [214, 215]. In fact, paroxysmal events with apnea in infants with achondroplasia may arise from a variety of causes: secondary to abnormalities at the craniocervical junction and consequent abnormality of central respiratory control; from primary seizures; from airway obstruction related to macrocephaly and hypotonia (e.g.…”
Section: Natural History and Managementmentioning
confidence: 99%
“…The FGFR3 gene, encoding a member of the fibroblast growth factor receptor family, has been reported to be exclusively expressed in the locus coeruleus in patients with major depressive disorder [89]. Previous studies have demonstrated that skeletal dysplasia patients with Asn540Lys mutation in the FGFR3 gene have been documented to accompany with medial temporal lobe dysgenesis and epilepsy [90][91][92].…”
Section: Discussionmentioning
confidence: 99%